Enhancing photocatalytic properties of continuous few-layer MoS2 thin films for hydrogen production by water splitting through defect engineering with Ar plasma treatment. (May 2023) - Huang, Yu-Sheng; Liu, Yan-Ting; Perng, Tsong-Pyng; Lu, Ming-Yen; Chueh, Yu-Lun; Chen, Lih-Juann
Abstract: Continuous few-layer MoS2 thin films composed of the stacked MoS2 nanoflakes were fabricated with a facile thermal decomposition method. These nanoflakes possess exposed active sites which are beneficial to the photocatalytic properties. Defect engineering with the aim to generate more exposed edges accompanied with abundant excited carriers by variation of Ar plasma power has been carried out. Positive results were indeed obtained. On the other hand, increasing exposed active edges/defects induced by Ar plasma was found to lead to the occurrence of oxidation in air with time. The variations of crystallinity, S/Mo ratio, and oxygen adsorption after Ar plasma treatment were investigated by high resolution transmission electron microscopy, high resolution x-ray analysis of photoemission spectroscopy as well as Raman spectroscopy. The few-layer MoS2 bombarded by Ar plasma with 30 W power provides the optimal photocatalytic enhancement in hydrogen production about 1.4 times reaching 246 mmolg − 1 h − 1 and the photocurrent density was increased by about 15 times to the pristine one. In addition, MoS2 /Au system from our previous survey is also utilized this method can generate 338 mmol / g − 1 h − 1, as high as 188% enhancement compared to pristine one. The increase in conductivity for Ar plasma treated MoS2 thin films is attributed to the formation of 2D phase of MoOx with higher electron mobility. The investigation has clarified the influence of defects on the photocatalytic performance. Nevertheless, the defects were found to be unstable when the samples were stored in the air. It is highly desired to pursue a scheme to stabilized the defects for practical applications. Graphical Abstract: Enhancing Photocatalytic Properties of Continuous Few-layer MoS2 Thin Films for Hydrogen Production by Water Splitting through Defect Engineering with Ar Plasma Treatment. ga1 Highlights: The Ar plasma treatment in few-layer MoS2 can improve the hydrogen productivity by about 1.4 times compared to the pristine one. Suitable power value of Ar plasma can induce sufficient excited carriers and exposed sites with possible MoOx phase transformation. The stability of samples after Ar plasma is the critical issue for further investigation.